A National Survey of the Nursing Care of Infants With Prenatal Substance Exposure in Canadian NICUs. (October 2015) - Marcellus, Lenora; Loutit, Tara; Cross, Shannon; Ikuta, Linda; Zukowsky, Ksenia
<x xml:space="preserve">Abstract</x> Background: Many communities are reporting increases in the number of infants requiring NICU care. Practices continue to vary and there is limited available evidence about nursing care. Purpose: The purpose of this study was to describe current nursing care practices for infants with prenatal substance exposure in the NICU setting and during transition to the community. Findings from this study were compared with an earlier Canadian survey (by Marcellus in 2002) to identify shifts in clinical nursing practice for this population. Methods: This was a cross-sectional descriptive survey design. A 68-item survey composed of multiple-choice and open-ended questions was administered through FluidSurveys online software. A convenience sample of 62 clinical managers or clinical educators in hospitals with active maternal-infant clinical units with 500 deliveries or more annually and/or pediatric hospitals with a separate designated neonatal service (ie, Level 2 and 3 units) was chosen. Results: A greater number of NICUs are using clinical guidelines to support the standardization of quality care. Improvements in nursing practice were identified and these included the consistent use of a withdrawal scoring tool and provision of education for team members in orientation. A decline in routine discharge planning meetings and routine parent teaching plans was discovered. Implications for Practice: This survey has improved understanding of the current state of nursing care for infants with prenatal substance exposure and their families during this critical time of transition. The purpose of the survey was to compare findings with the 2002 study by Marcellus to identify any improved practices and describe current state nursing care practices in the NICU. Practice changes over the last decade have included keeping mothers and infants together, expanding concepts of the team, integrating programs and services across hospital and community settings, and creating opportunities for NICU teams to learn more about substance use, mental health, violence, and trauma. Implications for Research: Focus on discharge planning, parent teaching, and creation and implementation of national/hospital guidelines is essential for consistent evidence-based quality patient care.